Pain relief and pain intensity response to GLP-1 receptor agonist ROSE-010 in irritable bowel syndrome; clinical study cross-analysis with respect to patient characteristics. (3rd July 2022) - Touny, Aya A.; Kenny, Enda; Månsson, Maria; Webb, Dominic-Luc; Hellström, Per M.
Abstract: Background and aims: Glucagon-like peptide-1 receptor agonist ROSE-010 has been studied for management of irritable bowel syndrome (IBS). ROSE-010 showed promising effects by reducing pain during attacks of IBS. In this exploratory substudy, we cross-analyzed earlier data to identify the most suitable subpopulation for treatment with ROSE-010. Methods: Data comprising 166 participants (116 females, 50 males) treated by subcutaneous injection with ROSE-010 at 100 µg and 300 µg versus placebo were broken down into subpopulations with recall of historical pain intensity, pain intensity immediately before treatment, gender, age, BMI, IBS subtype as well as pain intensity and pain relief of ROSE-010 with relationship to plasma glucose using visual analogue scores. Statistical cross-analysis was performed to detect optimal responders for adequate pain relief response. Results: ROSE-010 gave dose- and time-dependent effects with maximum pain relief at 300 µg relative 100 µg and placebo at 120 min post injection. Females had greater pain relief than males; age and BMI did not affect treatment response. IBS pain relief was greatest in constipation-dominant IBS (IBS-C) and mixed IBS (IBS-M) relative diarrhea-dominant and unspecified IBS. Conclusions: Clinical trial data indicate that female participants are more likely than males to respond to ROSE-010 100 µg and 300 µg to achieve meaningful IBS pain relief. Maximum pain relief was achieved at 120 min with the higher dose, although this was accompanied with higher rates of nausea. Improvement of IBS pain attacks was most pronounced in IBS-C and IBS-M, suggesting these subgroups to be optimal ROSE-010 responders.